An interfaith dialogue with Sir William Osler: crossing the divide of COVID-19 pandemic. Issue 5 (2nd September 2020) - Kopel, Jonathan; Webb, Mark
ABSTRACT: With the recent COVID-19 pandemic and George Floyd protests, the USA (US) has become extensively polarized across social and political divides. The COVID-19 pandemic has left tens of thousands dead and several million American citizens without work. Furthermore, the months of quarantine and uncertainty with the COVID-19 virus impacted the economic stability and health of Americans. In recent weeks, the divides have only deepened with the death of George Floyd from police brutality, which ushered in worldwide protests addressing racial, social, and law enforcement issues for minority groups. Both developments have ushered in unprecedented challenges for addressing social disparities while controlling the spread and devastation of the COVID-19 pandemic. With social media and mass communication, polarization between opposing groups has only deepened the divide. An inclusive dialogue that recognizes the intellectual and interpersonal boundaries of opposing groups would provide an avenue towards mutual understanding and further collaboration towards a common goal and solution. A physician that exemplified many aspects interfaith dialogue in his clinical practice and personal life was the late Sir William Osler. This will be accomplished through a fictional dialogue between Sir William Osler and Dr. Mark Webb.